OC-030 Barrett'S Epithelium Shows Evidence of Gastric and Intestinal Differentiation Programmes but Preserves the Proliferative and Stem Cell Architecture of Gastric Glands. (4th June 2013) - Lavery, D; Nicholson, A; Jeffery, R; Poulsom, R; Barr, H; Jankowski, J; Novelli, M; Shepherd, N; Rodriguez-Justo, M; Jansen, M; Wright, N A; Mcdonald, S A C
Abstract : Introduction: The origin and development of Barrett's oesophagus has long been discussed, with three main proposals for the origin of metaplasia: from oesophageal squamous epithelium, from upward migration of cardiac glands, or from submucosal glands. Methods: In Barrett's glands we have studied the distribution of proliferative activity using Ki67 and the migration of cells in Barrett's glands from patients infused with iododeoxyuridine 7 and 11 days pre-oesophagectomy. We have localised gene expression of mucins using immunohistochemistry (IHC) and trefoil family factor (TFF) peptides using IHC and in situ hybridization (ISH) and the stem cell marker Lgr5 using ISH, combining this with analysis of the clonal architecture of Barrett's glands using mitochondrial DNA (mtDNA) as a clonal marker. Results: In Barrett's glands proliferation is seen mainly in the middle part of the gland and diminishes towards the surface and the base of the gland. Cells migrate in a bidirectional manner. MUC5AC and TFF1 expression are found superficially, while MUC6 and TFF2 are found at the bases of the glands, similar to the distribution seen in antral gastric glands: MUC2, staining goblet cells and columnar cells, is concentrated superficially. Lgr5 mRNA is also found in the middle part of the glands, indicating the location of the stem cell niche. Barrett's glands are clonal, indicating derivation from a single cell, and suggesting that Barrett's stem cells have dual differentiation capacity. Gastric intestinal metaplasia, on the other hand, shows basal Lgr5 mRNA localisation with a distribution of proliferative activity similar to intestinal crypts. Conclusion: We conclude that Barrett's glands show the proliferative and stem cell architecture, and preserve patterns of gene expression of pyloric-type gastric glands, but are maintained by unique stem cells with both gastric and intestinal differentiation capacity: we propose that Barrett's glands originate as gastric glands and that subsequent intestinal differentiation advances with time, strongly supporting an origin from the proximal cardiac mucosa. Disclosure of Interest: None Declared